Exploring gene editing as a potential therapeutic strategy for hemophilia - Kumarasamy, Nishal; Balakrishnan, Balaji (Frontiers in Bioengineering and Biotechnology, 2026)
Hemophilia is an inherited bleeding disorder caused by mutations in the F8 or F9 gene, leading to a deficiency or dysfunction of coagulation factors VIII or IX. While current treatments, such as factor replacement, extended half-life factors, and gene therapy, have improved patient outcomes, they have limitations such as immunogenicity, transient transgene expression, and the requirement for high vector doses. Gene editing for hemophilia is an emerging approach that aims to provide a permanent cure by editing the mutated gene precisely or targeted integration of coagulation factor cDNA into the host genome for stable expression. This approach involves the use of programmable nucleases (CRISPR/Cas9, TALENs, ZFNs) that induce double-stranded DNA breaks at specific sites, allowing precise correction or targeted transgene integration. This review covers the various editing tools and strategies used for precise gene editing in hemophilia, including approaches such as HDR, NHEJ, base editing, prime editing, ex vivo gene editing in iPSCs, and recent LNP-based CRISPR delivery methods for precise editing.